Diseño e implementación del prototipo Ensambladora Luer-Cap - Fernández-Gamboa, Luis Ricardo (Instituto Tecnológico de Costa Rica, 2015)
The following document describes the design and implementation process of a prototype used in the automatic assembly of the tapa-conector subassembly. The project was conducted in the Baxter Productos Médicos manufacturing plant, where intravenous sets are produced using the aforementioned subassembly. This project arises as an opportunity to improve the current assembly process, in which the subassemblies are produced manually. The project was divided in two main areas, a feeder system for the Luer Lock and Vented Cap components, and an assembly system which joins this components to make the tapa-conector subassembly. During the development of the project, the prototype was designed and constructed using primarily 3D printed parts and components found within the plant. Once the prototype was finished, functionality tests were performed to detect the designs strengths and weaknesses. Finally, several recommendations were made regarding the automation of the process in question using the tests results.
Proyecto de Graduación (Licenciatura en Ingeniería en Mecatrónica) Instituto Tecnológico de Costa Rica, Área Académica de Ingeniería en Mecatrónica, 2015.
Keywords: Automatización; Prototipo; Alimentación